Enhanced performance via partial lead replacement with calcium for a CsPbI3 perovskite solar cell exceeding 13% power conversion efficiency. Issue 14 (16th March 2018) - Lau, Cho Fai Jonathan; Deng, Xiaofan; Zheng, Jianghui; Kim, Jincheol; Zhang, Zhilong; Zhang, Meng; Bing, Jueming; Wilkinson, Benjamin; Hu, Long; Patterson, Robert; Huang, Shujuan; Ho-Baillie, Anita
Abstract : Partial replacement of Pb in CsPbI3 perovskite solar cells with Ca enhances power conversion efficiency to 13.5% under reverse scan (stabilised at 13.3%), without sacrificing stability. Abstract : Cesium metal halides are potential light-harvesting materials for use in the top cells of multi-junction devices due to their suitable bandgaps and good thermal stabilities. In particular, CsPbI3 has a bandgap of 1.7 eV, which is suitable for perovskite/Si tandem cells. However, the desirable black phase for CsPbI3 is not stable because Cs is too small to support the PbI6 octahedra. Also, there is room for improvement in terms of cell performance. Herein, we partially replace Pb 2+ with Ca 2+ in the CsPbI3 precursor, producing multiple benefits. Firstly, more uniform films with larger grains are produced from CsPbI3 with Ca 2+, due to the reduction in the size of the colloids in the precursor solution with Ca 2+ . This morphology improvement provides better contact at the interface between the perovskite and the hole transport layer. In addition, it is found that the surface of the film is modified by the formation of a Ca rich oxide layer, providing a surface passivation effect. Finally, incorporation of Ca increases the band gap, leading to an increase in output voltage. The best CsPbI3 solar cell using 5% Ca 2+ substitution in the precursor achieves a stabilised efficiency of 13.3%, and maintains 85% of its initial efficiency for over 2 months with encapsulation.